To Restrain or Refrain: Determination of Parental Attitude towards the Child's Experience with Protective Stabilization - Ramadevi R. P; Hemamalini Rangarajan; Raj Santosh; Aravinth V; Vijila K. V; Yamunadevi Andamuthu (Wolters Kluwer Medknow Publications, 2024)
BackgroundTo overcome disruptive behavior of children, pediatric dentists rely on various behavior management techniques. When dental therapy is pertinent and nonaversive techniques like tell-show-do, voice control, and positive reinforcement are ineffective; the role of advanced behavior guidance techniques like physical restraints and protective stabilization is of paramount importance. AimThe study was carried out to elicit parents' opinion and record their response to their children's experience who underwent dental treatment with an extra assistant for protective stabilization. Materials and MethodsResponse was elicited to a questionnaire from 50 parents of children lacking cooperative ability and were exposed to an extra assistant for protective stabilization during various dental procedures. ResultsThe dental assistant was most preferred as the extra assistant to provide active stabilization. An overwhelming 98% of the parents agreed to protective stabilization with an extra assistant as advantageous and a good 88% of the parents recommended its use for further appointments of their children. ConclusionMajority of the parents approved protective stabilization with an extra assistant in future appointments of their children.